Associations between social support and proactive health behaviours among Chinese adolescents: the mediating role of self-efficacy and peer relationships - Zhiyuan Lu; Lianlong Yu; Kexin Fan; Tian Hu; Lin Liu; Suyun Li; Yunping Zhou (BMC, 2024)
Abstract Background Proactive health behaviours are crucial for enhancing adolescent health. However, there is limited evidence on the potential pathways through which social support influences adolescents' proactive health behaviours. This cross-sectional study aimed to examine the relationships between social support, self-efficacy, peer relationships and proactive health behaviours in Chinese adolescents. Methods From October to December 2023, we recruited 6075 adolescents from Shandong Province, China. They completed self-report questionnaires on social support, self-efficacy, peer relationships and proactive health behaviours. Results Linear regression analysis indicated that social support was positively associated with proactive health behaviours among adolescents (β = 0.571, 95% CI = 0.542, 0.600). Further mediation analyses revealed that self-efficacy (β = 0.085, 95% CI = 0.069,0.101) and peer relationships (β = 0.156, 95% CI = 0.136,0.177) mediated this relationship. Conclusions Increased social support was associated with better proactive health behaviours in Chinese adolescents. Additionally, higher self-efficacy and positive peer relationships enhanced this association. Our findings emphasised the significance of providing supportive environments at home and at school to promote proactive health behaviours in adolescents.